CONVERSATIONAL IMPLICATURE OF INDONESIAN STUDENTS IN DAILY CONVERSATION - Annisa Martini (Indonesian EFL Journal, 2018)
The research examined conversational implicature of Indonesian students of English Education Department in University of Kuningan in the daily conversation. The reason of choosing this topic was based on the problem in which people frequently produce utterances which are not informative or provide less or too much information as required in their daily conversation. This qualitative research used observation and recording to collect the data needed. As result, this research found 80 utterances indicating conversational implicature which consist of 32 utterances (40%) belonging to generalized conversational implicature and 48 utterances (60%) belonging to particularized conversational implicature. In conclusion, the utterances contain two types of conversational implicature and its function in conversation causing different assumption based on Tsuda’s theory such as violation of Grice’s cooperative principle, power and solidarity and joking indirect conversation. However, the functions itself are influenced by interpretation of the researcher as the listener or a reader.Keywords: conversational implicature, daily conversation, functions of conversational implicature, Indonesian students